The role of lithium in the treatment of bipolar depression - Bhagwagar, Z; Goodwin, G (2002)
Bipolar depression is assuming increasing importance as perhaps the major challenge in the acute management of bipolar 1 disorder. Treatment guidelines suggest an overwhelming expert preference for the use of lithium as first line treatment rather than antidepressants. However, the actual evidence for acute efficacy of lithium in bipolar depression, either as a sole agent or in combination with other drugs, is disappointing. Lithium still has an important role in maintenance treatment and appears to reduce the incidence of suicide, but its efficacy specifically against depression is beginning to be questioned. It remains nevertheless a key comparator for new studies in bipolar disorder. © 2002 Elsevier Science B.V. All rights reserved.